Hypercapnia alters stroma-derived Wnt production to limit β-catenin signaling and proliferation in AT2 cells - Laura A. Dada; Lynn C. Welch; Natalia D. Magnani; Ziyou Ren; Hyebin Han; Patricia L. Brazee; Diego Celli; Annette S. Flozak; Anthea Weng; Mariana Maciel Herrerias; Vitalii Kryvenko; István Vadász; et al. (JCI Insight, 2023)
Persistent symptoms and radiographic abnormalities suggestive of failed lung repair are among the most common symptoms in patients with COVID-19 after hospital discharge. In mechanically ventilated patients with acute respiratory distress syndrome (ARDS) secondary to SARS-CoV-2 pneumonia, low tidal volumes to reduce ventilator-induced lung injury necessarily elevate blood CO2 levels, often leading to hypercapnia. The role of hypercapnia on lung repair after injury is not completely understood. Here — using a mouse model of hypercapnia exposure, cell lineage tracing, spatial transcriptomics, and 3D cultures — we show that hypercapnia limits β-catenin signaling in alveolar type II (AT2) cells, leading to their reduced proliferative capacity. Hypercapnia alters expression of major Wnts in PDGFRα+ fibroblasts from those maintaining AT2 progenitor activity toward those that antagonize β-catenin signaling, thereby limiting progenitor function. Constitutive activation of β-catenin signaling in AT2 cells or treatment of organoid cultures with recombinant WNT3A protein bypasses the inhibitory effects of hypercapnia. Inhibition of AT2 proliferation in patients with hypercapnia may contribute to impaired lung repair after injury, preventing sealing of the epithelial barrier and increasing lung flooding, ventilator dependency, and mortality.